Cholelithiasis and Cholecystitis in Childhood - Wingert, Willis A. (1967)
Six cases of cholecystitis and cholelithiasis confirmed by x-ray examination and surgical operation were observed in a ten-year period. Due to the wide variability in signs and symptoms in children, cholecystitis and cholelithiasis can be diagnosed only with a high degree of clinical suspicion and roentgenological examination. Gallbladder disease is uncommon in childhood but should be considered in children with vague abdominal pains or bouts of unexplained jaundice. If a normal appendix is found at laparotomy in the “acute abdomen,” the surgeon would be wise to palpate other specific organs within the abdomen, including the liver and gallbladder. The treatment of choice is cholecystectomy. The prognosis for recovery is excellent if there is no complicating systemic disease.